INKONSISTENSI MAHKAMAH KONSTITUSI DALAM MENGADILI PERKARA BATAS USIA CALON WAKIL PRESIDEN - M Beni Kurniawan; Sri Ayu Ramadani (Komisi Yudisial RI, 2025)
The Constitutional Court’s inconsistency in adjudicating judicial review cases concerning the age requirement for vice-presidential candidates has set a precedent that undermines the Constitutional Court’s integrity and credibility. Judgment Number 90/PUU-XXI/2023 has attracted significant attention because, on the same day, the Constitutional Court rendered two judgments concerning substantially similar issues relating to the age requirement for vice-presidential candidates yet reached different rulings. This situation raises questions regarding the factors underlying the Constitutional Court’s inconsistency in adjudicating such cases. This study aims to analyse the cause of this inconsistency, and to formulate the appropriate ruling consistent with the legal reasoning of the constitutional court justices. This study employs a normative legal research method using a prescriptive approach through an analysis of the legal reasoning underpinning the judgment. The findings indicate that Judgment Number 90/PUU-XXI/2023 should have been limited to the office of governor, as this represented the common ground among the five constitutional justices who voted to grant the petition in part. Accordingly, the ruling should read: “at least 40 years of age or has served or is serving as a governor.” This study concludes that Constitutional Court’s inconsistency stems from three principal factors: the inconsistent application of the open legal policy doctrine, the judicialization of politics in judicial decision-making, and a conflict of interest arising in Judgment Number 90/PUU-XXI/2023. Accordingly, it is necessary to strengthen the standards for the application of the open legal policy doctrine and to enhance oversight mechanisms for potential conflicts of interest to safeguard the consistency of judicial decisions, institutional integrity, and public confidence in the Constitutional Court.